(3QSGdI aj GdETGQI HGdeSHMI aj GdUdGI MGd GdTgGOIs
(3ChdgG (B:s
(3GdMeO ddg GdPi Od Ydi GdNjQ hHYO aHYO eG cJHJ QSGdI eTJedI Ydi JMbjb eSCdI GdETGQI HGdeSHMI ai GdUdGI MGd GdTgGOI ai GdbYOI hHjfJ CfgG KGHJI s
(3BNQgG (B:s
(3gOGfG Gddg hEjGce EdiG dWQjb GdeSJbje hGdefgL Gdbhje hGdMeO ddg GdYXje hGdUdGg hGdSdGe Ydi QShdg GdcQje hUdi Gddg Ydjg hSde hYdi Bdg hUMHg CLeYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B22s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B136) s
Keywords: (3GdeLGejYs